PERSPEKTIF REMAJA PEREMPUAN KOTA MEDAN TERHADAP FITUR FD TALK “APLIKASI FEMALE DAILY” - Nasution, Elza Hasyim; Sazali, Hasan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
In today's digital era, teenagers have the convenience of learning new things and following beauty trends through various available platforms and media. One platform that is presented to be able to follow beauty trends is Female Daily. This study aims to analyze the perspectives of young women in the city of Medan on the FD Talk feature on the Female Daily application. The research method used is qualitative research using in-depth interview techniques with 3 sources of informants who actively use FD Talk. Data collection techniques were carried out through observation and interviews of young women in the city of Medan. The analysis was carried out using the theory of TAM to understand user perceptions about usability, ease of use, and attitudes toward using the application and also using interpersonal communication theory. The results showed that the features of FD Talk succeeded in building positive perceptions of usability and ease of use in the eyes of the users. The speakers found it useful to learn about skincare and beauty from the personal experiences of other users on the platform. In addition, a good and easy-to-understand interface is also a factor that makes users feel comfortable using the application.